Motivasi Anak-Anak Usia 9 – 12 Tahun Dalam Mengikuti Latihan Sepak Bola Di KLUB Amatir Putra Junior Banyuwangi - Naufal Al’fath Firjatullah; Lutfhi Abdil Khuddus (Universitas Palan, 2024)
Motivation is an encouragement that a person has to do something to achieve the goal or what he wants. This research is motivated by the results of an initial survey of researchers discussing with coaches and player guardians, for the beginning of 2022 the players at the Putra Junior club were 30 senior players and for young ages there were still none. But over time players for young ages, namely ages 9-12 years at the Putra Junior club, arrived to take part in football training at the Putra Junior club. The arrival of players aged 9-12 years does not necessarily want to take part in training, but there is a sense of desire or encouragement to want to take part in football training from themselves and from their parents. Therefore, researchers want to know the level of desire and encouragement called motivation. The purpose of this study was to determine the level of motivation of players aged 9 to 12 years in participating in football training at the Putra Junior club. This research was conducted on May 2, 2023 at Kanalan Field, Banyuwangi Regency, using the total sampling technique, the entire population was sampled for this study, with 30 participating players. This research uses a method with data collection with a closed questionnaire. The data analysis technique used is quantitative descriptive analysis. It is known from the results of quantitative descriptive analysis that the motivation of 9-12 year old players in participating in football training at the Putra Junior club in the very high category is 10%, high 23%, moderate 40%, low 23%, and very low 3%. The results of the analysis show that the motivation of players aged 9 to 12 years following football training at the Putra Junior club is 40% in the medium category.